Influence of Soap and Different Textile Materials on Possibility of Determination Origin Traces of Blood in Forensic - Medicine and Criminology Investigation - Milosavljević, Mladen (Kriminalističke teme, 2002)
In this work author tray find, influence (effect) different soap (eight different soap with different pH value) and different textile material (ten different textile bases with different fibers - fibers of natural origin and fibers of artificial - chemical) on possibility determination origin traces of blood in criminology investigation, and forensic - medicine investigation. This examination showed some early experience (very rarely experience and insufficient information) and results, that in this situations different soap and different textile bases does not effect on this level (determination of origin) investigation traces of blood. During examination this experiment is corfirm high sensitive test for determination origin traces of blood, and this work has one new quality. In this work author tray detect possibility influence pH value from dfferent soap on this level investigation. DNA analyze is very important, but some classical techniques will always have their value.